A super absorbent polymer containing copper to control Plenodomus tracheiphilus the causative agent of mal secco disease of lemon - El boumlasy, Soumia; La Spada, Federico; Pane, Antonella; Licciardello, Antonino; Debdoubi, Abderrahmane; Tuccitto, Nunzio; Cacciola, Santa Olga (Frontiers in Microbiology, 2022)
The aim of this study was to determine the effectiveness of a Super absorbent polymer (SAP) containing copper (SAP-Cu) in controlling mal secco disease (MSD) of lemon caused by the fungus Plenodomus tracheiphilus. Super absorbent polymer containing copper was characterized by atomic absorption spectrometry (AAS) and UV-VIS spectroscopy. In vitro tests were performed to determine the inhibitory effects of SAP-Cu against the pathogen on both potato-dextrose-agar medium and naturally infected lemon cuttings. Super absorbent polymer was able to absorb up to about 200 and 30 times its weight of ionized water and copper (II) sulfate solution (Cu2+ ions at the concentration 236 mM), respectively. The distribution of copper released on twigs after 24 h of contact with SAP-Cu was determined by secondary ion mass spectrometry with time-of-flight analyzer (ToF-SIMS). Super absorbent polymer containing copper significantly inhibited the viability of P. tracheiphilus in lemon twigs. Overall, the results of this study showed that the SAP could be a suitable carrier of antifungal compounds.